Most Small Cerebral Cortical Veins Demonstrate Significant Flow Pulsatility: A Human Phase Contrast MRI Study at 7T - Driver, Ian D.; Traat, Maarika; Fasano, Fabrizio; Wise, Richard G. (Frontiers in Neuroscience, 2020)
Phase contrast MRI has been used to investigate flow pulsatility in cerebral arteries, larger cerebral veins and the cerebrospinal fluid. Such measurements of intracranial pulsatility and compliance are beginning to inform understanding of the pathophysiology of conditions including normal pressure hydrocephalus, multiple sclerosis and dementias. We demonstrate the presence of flow pulsatility in small cerebral cortical veins, for the first time using phase contrast MRI at 7 Tesla, with the aim of improving our understanding of the haemodynamics of this little-studied vascular compartment. A method for establishing where venous flow is pulsatile is introduced, revealing significant pulsatility in 116 out of 146 veins, across 8 healthy participants, assessed in parietal and frontal regions. Distributions of pulsatility index and pulse waveform delay were characterized, indicating a small, but statistically significant (p<0.05), delay of 59±41 ms in cortical veins with respect to the superior sagittal sinus, but no differences between veins draining different arterial supply territories. Measurements of pulsatility in smaller cortical veins, a hitherto unstudied compartment closer to the capillary bed, could lead to a better understanding of intracranial compliance and cerebrovascular (patho)physiology.